ANXIETY AND DEFENSE MECHANISM BY THE MAIN CHARACTER IN LALA BOHANG’S WAKING UP FOR THE FIRST TIME (2021) - Usi Putri Lestari; Anita Sari (JEELL (Journal of English Education, Linguistics and Literature), 2026)
Anxiety is one of the most pervasive psychological experiences in modern life and is frequently represented in literary works as a reflection of human emotional struggles.  This study aims to examine how anxiety is portrayed and how defense mechanisms are employed by the main character in Lala Bohang’s Waking Up for the First Time (2021). Using Sigmund Freud’s psychoanalytic theory, this qualitative descriptive study focuses on the main character as the participant of the research. The data consists of narrative passages and dialogues reflecting anxiety and defensive behavior. Data were collected through close and repeated reading of the literary work and analyzed using textual interpretation based on Freud’s concepts of anxiety and defense mechanisms. The findings reveal that the main character experiences three forms of anxiety: neurotic, moral, and realistic anxiety. To cope with these psychological pressures, she employs repression, denial, projection, displacement, and sublimation. While the first four mechanisms provide temporary relief, sublimation enables the transformation of anxiety into constructive behavior and personal growth. The study concludes that anxiety plays a significant role in shaping the character’s psychological development. These findings support the application of psychoanalytic theory in literary criticism and contribute to a deeper understanding of the representation of psychological experiences in literature.